1988
DOI: 10.1177/019262338801600402
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure and Histology of Hepatocellular Carcinomas of English Sole (Parophrys vetulus) from Puget Sound, Washington

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…These authors identified the fibrils as dilated rough endoplasmic reticulum (RER) containing microfilamentous material. Unlike Stehr et al (1988), h o w ever, we found these structures exclusively in nontumorous cells, even in the case of one llver which contained a carcinoma.…”
Section: Focl Of Cellular Alteration ] Hydropic Vacljoliution Of Bilicontrasting
confidence: 55%
See 1 more Smart Citation
“…These authors identified the fibrils as dilated rough endoplasmic reticulum (RER) containing microfilamentous material. Unlike Stehr et al (1988), h o w ever, we found these structures exclusively in nontumorous cells, even in the case of one llver which contained a carcinoma.…”
Section: Focl Of Cellular Alteration ] Hydropic Vacljoliution Of Bilicontrasting
confidence: 55%
“…Using light microscopy, the resulting structures resembled the fibrillar hepatocytes described by Stehr et al (1988) in hepatocellular carcinomas of English sole. A similar finding was reported by Kohler (1989) in non-tumourous liver in European flounder.…”
Section: Focl Of Cellular Alteration ] Hydropic Vacljoliution Of Bilimentioning
confidence: 67%
“…It is difficult to classify species absolutely since many factors affect the amount of storage material within the hepatocytes. Differences in types of storage material may even exist among specimens of the same species, as has been demonstrated in English sole (Pleuronectes vetulus) (Stehr et al 1988).…”
Section: Discussionmentioning
confidence: 91%
“…In sexually mature flatfish species, such as European flounder (Platichthys flesus), winter flounder (Pseudopleuronectes americanus), and plaice (Pleuronectes platessa), the pancreatic tissue is more scattered throughout the liver (Timashova 1982;Ko¨hler 1990;Murchelano and Wolke 1991;March and Reisman 1995;Vethaak and Wester 1996). As in other fish, the histomorphology of the liver in sexually immature L. ferruginea causes difficulties in determining the functional liver units and in explaining the appearance of histopathological changes (Hampton et al 1985(Hampton et al , 1988Morrison 1987;Stehr et al 1988;Ko¨hler 1989;Krause and Cutts 1994;Vethaak and Wester 1996). In vivo microscopy of liver microvasculature in rainbow trout revealed a repeating pattern of alternation between afferent and efferent regions (Hinton and Lauren 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation